A survey of cloud computing migration issues and frameworks. - Cardoso, Abílio (2014)
The cloud computing paradigm is transforming the way IT services are provided and consumed. The moving of in-house IT services to the cloud- computing paradigm should be performed carefully lest cause high losses in the institution that is in the process of transition to cloud computing. So, in this paper, we presents a study of several frameworks developed to move IT services and applications to the cloud computing.